Anticipation in the cognitive structure of speechreading in deaf pupils - D. Georgieva; A. Koleva; G. Valchev (Trakia Journal of Sciences)
Anticipation is one of the basic components in the cognitive structure of speechreading. In order to study the probability prediction ability, determining the skills for correct decoding and interpretation of visually perceived oral information by deaf people; an experiment has been carried out involving 91 pupils aged between 7 and 12, integrated into general education schools. Participants in the study have a hearing loss of ≥90 dB. The results obtained demonstrate a high degree of correlation between linguistic and meaningful prediction ability and children’s speechreading skills. There is also a directly proportional relationship between the chronological age of the students and the level of development of their anticipation ability.